DINAMIKA WAKAF DI INDONESIA (KAJIAN KOMPETENSI PERADILAN AGAMA) - Abd Khalik Latuconsina (IAIN Ambon, 2013)
The property that may be provided as waqf is more in the form of unmoving objects, so its allotment is not maximum for the social benefit. In addition, the community comprehension on waqf is more dominant positioned as object that may not be changed, including for being empowered. It causes the waqf property less productive for maximally social benefit. Majority of wakif from Indonesian Muslims have held to the conservative view of Asy-Syafi'i stating that the waqf property may not be exchanged for any reason. The waqf practices applied in Indonesia is still carried out conventionally which vulnerable to cause various problems and not a little that end up in the court. In this regard the Religious Court has authorities to resolve the case of waqf. Keywords: waqf, competency, religious courts